2017
DOI: 10.1111/iej.12785
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of cytotoxicity, genotoxicity and immunological inflammatory biomarker activity of several endodontic sealers against immortalized human pulp cells

Abstract: Martinho FC, Camargo SEA, Fernandes AMM, Campos MS, Prado RF, Camargo CHR, Valera MC. Aim To establish an SV40 T-Ag-transfected cell line of human pulp-derived cells in order to compare the cytotoxicity, genotoxicity and to investigate the activities of immunological biomarkers of several endodontic sealers. Methodology Primary human pulp cells and transfected cells were cultured. Cell morphology and proliferation were analysed, and the expression of cell-specific gene transcripts and proteins was detected by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
24
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 48 publications
0
24
0
1
Order By: Relevance
“…Apexit Plus shows low or no cytotoxicity effect on L929 mouse fibroblasts [10] and human periodontal ligament fibroblasts [9]. Moreover, no genotoxicity was induced by Apexit Plus on an immortalized cell line derived from human pulp [38]. Our morphological analysis showed that inflammatory cells were gradually replaced by fibroblasts distributed among bundles of collagen fibers in the capsules of all groups over time.…”
Section: Biological Propertiesmentioning
confidence: 72%
“…Apexit Plus shows low or no cytotoxicity effect on L929 mouse fibroblasts [10] and human periodontal ligament fibroblasts [9]. Moreover, no genotoxicity was induced by Apexit Plus on an immortalized cell line derived from human pulp [38]. Our morphological analysis showed that inflammatory cells were gradually replaced by fibroblasts distributed among bundles of collagen fibers in the capsules of all groups over time.…”
Section: Biological Propertiesmentioning
confidence: 72%
“…On the other hand, Martinho et al . (), using pulp cells in contact with extracts of different sealers, among them AHP, found higher levels of IL‐6 and an absence of difference for IL‐12 when compared to the control group. Those differences could be related to the cell model used, experimental design regarding sealer contact with cells and sealer composition.…”
Section: Discussionmentioning
confidence: 95%
“…Controversy exists regarding the choice of permanent cell lines or primary cell cultures as study models (Honegger , Martinho et al . ). Despite the greater use of permanent lineage cultures, these have unnatural behaviour, altering the biological responses against materials (Honegger ).…”
Section: Discussionmentioning
confidence: 97%
“…After setting, the toxicity decreases and may be null after 2 weeks. 12,13,20 In this study, the samples to obtain the extracts were used after setting, even so, the AH Plus commercial sealer (0%) showed a reduction in HGF cell viability due to a higher concentration of substances released for the medium in 7 days. In addition, the incorporation of the AgVO 3 into AH Plus in higher concentrations (5 and 10%) decreased the cell viability.…”
Section: Discussionmentioning
confidence: 99%
“…The components of the sealers may present cytotoxicity to human and animal cells, such as zinc oxide, eugenol, formaldehyde, resinous components, and calcium hydroxide, 12 causing inflammation and affecting DNA, thereby leading to genome instability and promoting carcinogenesis. 13 Within the nanoparticles, these can interact with cellular components, including DNA, proteins, and lipids, which may damage the integrity of the membrane depending on the chemistry of its surface. 14 The cytotoxicity of AgVO 3 to Daphnia similis, an aquatic organism, was evaluated by Artal et al 15 who attributed the cytotoxic effect observed to silver.…”
mentioning
confidence: 99%